Students’ Perception of Blended Learning at Junior High School (Combination of Synchronous and Asynchronous Learning) - Ni Komang Sri Mariati; Luh Putu Artini; Ni Putu Era Marsakawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Since the pandemic era, the process of teaching and learning has changed. Teachers and educators need to choose the appropriate learning model. This study aims to find out the suitable model learning between two models there are synchronous and asynchronous learning models. The study involved two classes, A-class (32 students) and B-class (35 students) of seven grade students at SMP Negeri 2 Tejakula. Data was collected by online questionnaire and shared via WhatsApp. The data were analyzed with the descriptive qualitative method by counting the mean of the Likert scale. The result shows that the student prefers to choose the asynchronous learning model, with the percentage of asynchronous learning at 69% and the synchronous learning model at 63%. It indicates two learning models can be implemented, but the suggestion to the teacher uses the asynchronous model to gain students’ participation.